Production of Xylanase from Arthrobacter sp. MTCC 6915 Using Saw Dust As Substrate under Solid State Fermentation. (2nd October 2011) - Murugan, Sevanan; Arnold, Donna; Pongiya, Uma Devi; Narayanan, P.M.
Abstract : Saw dust was used as substrate for xylanase production from Arthrobacter sp. MTCC 6915. The study of period of incubation, temperature, pH, carbon, and nitrogen sources for xylanase production was optimized. Xylanase production was found to be optimum at an incubation period of 96 hrs (117.0 U/mL), temperature 30°C (105.0 U/mL), and pH 9.0 (102.9 U/mL). The results showed that the xylanase production was found to be higher in the presence of carboxymethylcellulose (176.4 U/mL) and dextrose (126.0 U/mL). It was also observed that peptone (170.1 U/mL) and beef extract (161.7 U/mL) supported maximum xylanase production.The enzyme was characterized and found to be fairly active at pH 9 (764.4 U/mL) and temperature 60°C (819 U/mL). Even in the present study, a major difference in the production temperature (30°C) and optimal temperature (60°C) of the enzyme activity was observed. However, the pH of the production media and the enzyme activity were found to be the same (pH 9).